2022
DOI: 10.1186/s13046-022-02416-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HSP 90 is associated with potent anti-tumor activity in Papillary Renal Cell Carcinoma

Abstract: Background There is no universally accepted treatment for patients with advanced papillary renal cell carcinoma (PRCC). The presence of activating mutations in MET, as well as gain of chromosome 7, where the MET gene is located, are the most common genetic alterations associated with PRCC, leading to the clinical evaluation of MET tyrosine kinase inhibitors (TKIs) in this cancer. However, TKIs targeting MET selectively, as well as multitargeted TKIs with activity against MET demonstrate modest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In a study on the comprehensive molecular characterization of PRCC, alteration of the MET gene (mutation, splice variant, or gene fusion) or gain of chromosome 7 copy number was identified in 81.3% of Type 1 tumor 38 . Two pathways about PI3K/AKT and MEK/ERK1/2 pathways are important mediators of PRCC tumorigenesis through their roles in promoting cell growth 39 . Using multiple public genetic datasets, enolase 2 was found to increase glycolysis and cell proliferation, leading to a worse prognosis 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on the comprehensive molecular characterization of PRCC, alteration of the MET gene (mutation, splice variant, or gene fusion) or gain of chromosome 7 copy number was identified in 81.3% of Type 1 tumor 38 . Two pathways about PI3K/AKT and MEK/ERK1/2 pathways are important mediators of PRCC tumorigenesis through their roles in promoting cell growth 39 . Using multiple public genetic datasets, enolase 2 was found to increase glycolysis and cell proliferation, leading to a worse prognosis 40 .…”
Section: Discussionmentioning
confidence: 99%
“… 38 Two pathways about PI3K/AKT and MEK/ERK1/2 pathways are important mediators of PRCC tumorigenesis through their roles in promoting cell growth. 39 Using multiple public genetic datasets, enolase 2 was found to increase glycolysis and cell proliferation, leading to a worse prognosis. 40 Multi‐omics profiling of PRCC disclosed an increasing glutathione level, which is the main substance to overcome reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…71 Beyond the well-known HSP90 clients like the tumor suppressor p53 and the oncoprotein SRC, a myriad of other HSP90 clients, including protein kinases, telomerase, hypoxia-inducible factor 1α (HIF-1α), and Akt, are deeply entrenched in the processes that fuel tumor growth. 23,[111][112][113] It is worth noting that tumors exhibit a significant upregulation of HSP90 levels, and heightened HSP90 expression in breast cancer, for instance, has been linked to reduced patient survival rates. 114 Consequently, HSP90 stands as a pivotal enabler of oncogene addiction and a key player in facilitating the survival of cancer cells, and inhibition of HSP90 can lead to the degradation of these client proteins, making it a target for anticancer therapies.…”
Section: Hsp90 In Cancermentioning
confidence: 99%
“…HSP90, functioning as a molecular chaperone, assumes a critical role in promoting the survival of cancer cells, largely because of the substantial reliance of these cells on HSP90‐assisted signaling pathways 71 . Beyond the well‐known HSP90 clients like the tumor suppressor p53 and the oncoprotein SRC, a myriad of other HSP90 clients, including protein kinases, telomerase, hypoxia‐inducible factor 1α (HIF‐1α), and Akt, are deeply entrenched in the processes that fuel tumor growth 23,111–113 . It is worth noting that tumors exhibit a significant upregulation of HSP90 levels, and heightened HSP90 expression in breast cancer, for instance, has been linked to reduced patient survival rates 114 .…”
Section: The Relationship Between Hsp90 and Various Diseasesmentioning
confidence: 99%
“…A recent study demonstrated that plasma HSP90α level can be used as a prognostic biomarker for hepatocellular carcinoma [ 172 ]. HSP90 inhibition might be a novel strategy for advanced papillary renal cell carcinoma [ 173 ], metastatic triple-negative breast cancer [ 174 ], pancreatic carcinoma [ 175 ], prostate cancer [ 176 ], and glioma [ 177 ] treatment. HSP90 inhibition also improves the survival of patients with gastrointestinal stromal tumors [ 178 ] and overcomes resistance to molecular targeted therapy in glioma [ 179 ].…”
Section: Direct Impact Of Necrotic Products On Malignant Cells—role O...mentioning
confidence: 99%